Distribution of CCL3L1 copy number variable gene among three major ethnic groups in Malaysia - Jamaluddin, Jalilah (2017)
C-C motif Chemokine Ligand 3 Like 1 (CCL3L1) is one of the copy number variable genes which clustered within the hotspot for segmental duplication at chromosome 17q12. Many studies from different populations reported that common range copy number of this gene are from 0 – 14 copies. Variable copies of this CCL3L1 has been proven to correlate with a number of diseases such as Human Immunodeficiency Virus (HIV)-1 infection, tuberculosis (TB), Kawasaki disease, rheumatoid arthritis, Crohn’s disease, Systemic Lupus Erythematosus (SLE), Hepatitis C and Psoriasis as this gene plays a crucial role in hosts defending and immunoregulatory process. However, investigation on the variable copies of CCL3L1 in Asia region is less studied and there is no exclusive report from Malaysia which is known as multi-ethnicities country. Furthermore, Malaysia is also not exceptional to some of those diseases for examples Human Immunodeficiency Virus (HIV)-1 infection and tuberculosis. Hence, the finding of copy number associate to the related diseases should be carried out in Malaysia. Thus, the major aim of this study was to comprehensively examine the distribution of CCL3L1 variable copies in reference Malaysian including three major ethnics; Malays, Indians and Chinese. The distribution of CCL3L1 copy number between Malaysian and European populations were also compared. Paralogue Ratio Test (PRT) was performed in order to quantify the CCL3L1 copies among 178 Malays, 125 Chinese and 90 Indian, and microsatellite analysis was used as a validation tool. PRT is capable of amplifying test and reference regions simultaneously in one PCR reaction by a set of primers. PCR products from PRT and microsatellites assays were then electrophoresed via capillary electrophoresis, and different length of fragments produced was analysed by Peak Scanner Software. One-way ANOVA and independent student T-test were used to analyse the data obtained. This study demonstrated that the CCL3L1 copies were significantly different (p<0.0001) between three major ethnics; Malay, Chinese and Indian with the range of zero to eight copies, zero to ten copies, and zero to eight copies respectively. The mean (median) calculated for Malay, Chinese and Indian were 2.759 (2.869), 3.453 (3.290), and 2.437 (1.970) respectively. Additionally, Malaysian population possess copy number of CCL3L1 ranged from zero to ten copies and it was significantly varied when compared to the European population with the p-value of <0.0001. As the conclusion, CCL3L1 copy number has shown a variation among three major ethnics in Malaysia and subsequently showed a significant difference when compared to the European population. This study offers a fundamental approach in investigating a correlation to susceptibility of related diseases in the future.